Computer-aided architectural design futures : the next city -- new technologies and the future of the built environment : 16th International Conference, CAAD Futures 2015, São Paulo, Brazil, July 8-10, 2015. Selected papers /: the next city -- new technologies and the future of the built environment : 16th International Conference, CAAD Futures 2015, São Paulo, Brazil, July 8-10, 2015. Selected papers. (2015) - Unknown
No abstract available